Art and archaeology of the Erligang civilization (Publications of the Department of Art and Archaeology, Princeton University, 2014)
Erligang bronzes and the discovery of the Erligang culture / Robert Bagley -- Erligang : a perspective from Panlongcheng / Zhang Changping -- China's first empire? : interpreting the material record of the Erligang expansion / Wang Haicheng -- Civilizations and empires : a perspective on Erligang from early Egypt / John Baines -- Erligang : a tale of two "civilizations" / Roderick Campbell -- The politics of maps, pottery, and archaeology : hidden assumptions in Chinese Bronze Age archaeology / Yung-ti Li -- Erligang and the southern bronze industries / Kyle Steinke -- Erligang contacts south of the Yangzi River : the expansion of interaction networks in early Bronze Age Hunan / Robin McNeal -- Bronzes and the history of Chinese art / Maggie Bickford